Profile and perspectives of patients with hearing impairment: experience of a hearing camp conducted in rural Assam - Akhtar, Hanifa; Shunyu, Neizekhotuo B.; Khound, Murchana; Kaushik, Jaya Shankar; Bhattacharyya, Himashree; Jamil, M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Hearing aid non-compliance and rejection despite possessing the hearing aid, is widespread among hearing impairment, influenced by diverse factors. There is limited literature on perspectives of patient before enrolling them in hearing aid programmes at health camps. This cross-sectional study explored the socio-demographic profiles and perspectives of patients with hearing impairment towards their hearing problems and hearing aids, who attended a hearing camp in rural Assam. Methods: A community based cross sectional study was performed among patients attending hearing camp in the rural area of Kamrup district of Assam. Demographic details along with findings of ear, nose and throat examination and audiometry and perspectives of the patients on use of hearing aid were recorded in pre-validated questionnaire. Results: Out of 96 patients, 56 (62.9%) had hearing difficulties causing communication issues, social inactivity, and irritation among family members. Most attended the camp for free checkups and hearing aids. High treatment costs significantly delayed care for hearing-impaired patients compared to those with normal hearing. Conclusions: High treatment cost is barrier to use of hearing aid in rural Guwahati, provision of free hearing aid in hearing camps can serve to address this gap. Understanding these barriers and challenges faced by hearing impaired population of the rural population of India is essential to design the implementation of hearing screening and rehabilitation at the community level.